Zad.3
3x+7=21
5x-1=19
-3x-3=-15
-4x+2=18
3x-7=-1
9-2x=23
-2-4x=10
-6-2x=12
14+5x=-1
8x+7=39

Zad.4
5x-3-2x=15
6x+1+x=15
-4x-2+10x=10
-x-4-x-1=-9
4-2x-x=-14
1-x-2+5x=7
-8x-2+5x-9=4
10x-4x+2=20
4=-6x-2+4x
-15=x-9+5x
Daje Naj


Odpowiedź :

Odpowiedź:

zad.3

3x+7=21

3x = 21 - 7     /:3

x = 14/3 = 4 2/3

5x-1=19

5x = 19 + 1      /:5

x = 20/5 = 4

-3x-3=-15

-3x = -15 + 3      /:(-3)

x = 12/3 = 4

-4x+2=18

-4x = 18 - 2        /:(-4)

x = -16/4 = -4

3x-7=-1

3x = -1 + 7        /:3

x = 6/3 = 2

9-2x=23

-2x = 23 - 9      /:(-2)

x = -14/2 = -7

-2-4x=10

-4x = 10 + 2        /:(-4)

x = -12/4 = -3

-6-2x=12

-2x = 12 + 6      /:(-2)

x = -18/2 = -9

14+5x=-1

5x = -1 - 14        /:5

x = -15/5 = -3

8x+7=39

8x = 39 - 7      /:8

x = 32/8 = 4

Zad.4

5x-3-2x=15

3x = 15 + 3       /:3

x = 18/3 = 6

6x+1+x=15

7x = 15 - 1       /:7

x = 14/7 = 2

-4x-2+10x=10

6x = 10 + 2        /:6

x = 12/6 = 2

-x-4-x-1=-9

-2x = -9 + 5        /:(-2)

x = 4/2 = 2

4-2x-x=-14

-3x = -14 - 4        /:(-3)

x = 18/3 = 6

1-x-2+5x=7

4x = 7 + 1     /:4

x = 8/4 = 2

-8x-2+5x-9=4

-3x = 4 + 11         /:(-3)

x = -15/3 = -5

10x-4x+2=20

6x = 20 - 2        /:6

x = 18/6 = 3

4=-6x-2+4x

-2x = 4 + 2        /;(-2)

x = -6/2 = -3

-15=x-9+5x

6x = -15 + 9     /:6

x = -6/6 = -1

Szczegółowe wyjaśnienie:

Odpowiedź:

---------------------------------------------------------

zad.3

•3x+7=21

3x = 21 - 7 /:3

x = 14/3 = 4 2/3

•5x-1=19

5x = 19 + 1 /:5

x = 20/5 = 4

•-3x-3=-15

-3x = -15 + 3 /:(-3)

x = 12/3 = 4

•-4x+2=18

-4x = 18 - 2 /:(-4)

x = -16/4 = -4

•3x-7=-1

3x = -1 + 7 /:3

x = 6/3 = 2

•9-2x=23

-2x = 23 - 9 /:(-2)

x = -14/2 = -7

•-2-4x=10

-4x = 10 + 2 /:(-4)

x = -12/4 = -3

•-6-2x=12

-2x = 12 + 6 /:(-2)

x = -18/2 = -9

•14+5x=-1

5x = -1 - 14 /:5

x = -15/5 = -3

•8x+7=39

8x = 39 - 7 /:8

x = 32/8 = 4

---------------------------------------------------------

Zad.4

•5x-3-2x=15

3x = 15 + 3 /:3

x = 18/3 = 6

•6x+1+x=15

7x = 15 - 1 /:7

x = 14/7 = 2

•-4x-2+10x=10

6x = 10 + 2 /:6

x = 12/6 = 2

•-x-4-x-1=-9

-2x = -9 + 5 /:(-2)

x = 4/2 = 2

•4-2x-x=-14

-3x = -14 - 4 /:(-3)

x = 18/3 = 6

•1-x-2+5x=7

4x = 7 + 1 /:4

x = 8/4 = 2

•-8x-2+5x-9=4

-3x = 4 + 11 /:(-3)

x = -15/3 = -5

•10x-4x+2=20

6x = 20 - 2 /:6

x = 18/6 = 3

•4=-6x-2+4x

-2x = 4 + 2 /:(-2)

x = -6/2 = -3

•-15=x-9+5x

6x = -15 + 9 /:6

x = -6/6 = -1

---------------------------------------------------------

Szczegółowe wyjaśnienie:

Mam nadzieję że pomogłam :)